Exacerbation of COPD in elderly people admitted to a University Hospital in West Paraná (Research, Society and Development, 2024)
Objective: the aim of this study is to select patients diagnosed with Chronic Obstructive Pulmonary Disease - COPD who have an exacerbation of it, admitted to a university hospital in Paraná, Brazil. Methodology: This is an observational, retrospective, quantitative and analytical study. Data contained in the electronic medical records of patients admitted to the Hospital Universitário do Oeste do Paraná – HUOP were used. The sample of the present study was composed of all patients admitted to HUOP with a diagnostic hypothesis of exacerbated COPD, from March 2019 to February 2023, meeting the criteria of age > 60 years of both sexes with a diagnostic hypothesis of exacerbated COPD. Results: A total of 209 medical records were considered eligible for this study. Of these, 56.4% (118) were male, average age was 73.6 years, 90% (190) of patients had a history of smoking, 97.3% underwent physiotherapy during hospitalization and mortality was 46.4%. Conclusion: Hospitalization has deleterious effects on the functional capacity of elderly patients with COPD exacerbation, on the other hand, those who had early mobilization associated with physiotherapy showed a satisfactory evolution